Coal rates in electricity production. The reality of climate causes - Kovács, Ferenc (НТУ "ХПІ", 2013)
Recently, certain political, social and governmental groups have put down the changes in the Earth’s climate to the effect of carbon dioxide (CO₂) of anthropogenic (human, industrial) origin. The first part of the paper provides important arguments to refute this view. Then, through the analysis of the rates of primary fuels in electricity production, it is proven what a significant rate coal types represent in the world and in some leading countries. It is also presented in detail what rates are forecast in electricity supply for the future (2020, 2035, 2050). Comments are made about the fact that in spite of her significant coal resources that can be economically exploited, Hungary is planning an unjustifiably low (4%) coal rate.

Останнім часом певні політичні, соціальні і урядові групи ослабили свою увагу до змін в Земному кліматі, які відбуваються при викидах в атмосферу углексилого газу (CO₂) антропогенного (людський, індустріальний) походження. Перша частина статті присвячена аргументам, які спростовують ці твердження. З використанням аналізу норм використання палива у виробництві електрики, доведено, що існуючі типи вугілля можуть безпечно використовуватися у світі і в деяких лідируючих країнах. Представлені норми використання вугілля для виробництва електроенергії на перспективний період (2020, 2035, 2050). Приведені висновки про те, що, незважаючи на великі економічно доцільні можливості Угорщини по використанню вугілля для виробництва електроенергії, цей вид палива використовується недостатньо - всього на рівні 4%.
Keywords: fuel; norms of expense; economic efficiency; production of electric power; coal; паливо; норми витрати; ефективність економічна; виробництво електроенергії; вугілля